TEKNIK PENERJEMAHAN KONJUNGSI وَ (WA) ATAU “DAN” DALAM SURAT Al-ISRA’ - Kholida, Masita Taufiqi; Irfan, Irfan (Fakultas Teknik Universitas Negeri Makassar, 2025)
This research examines the translation techniques of the conjunctions “dan” or “wa” in Surah Al-Isra’ verses 1-111. This study is a type of qualitative research with comparative descriptive analysis. This is done by comparing the conjunctions “wa” and “dan” between the Arabic source text (ST) and the Indonesian target text (TT). The results obtained are: 182 data of the conjunction “wa” in Surah Al-Isra’ verses 1 to 111. The conjunction “wa” in the translation results has a connection pattern; 1) between words as many as 9 data, 2) between phrases as many as 13 data, 3) between sentences as many as 160 data. The conjunction pattern between sentences is the most used, while the conjunction pattern between words is the least used. The translation techniques found are 3 techniques (literal, reduction, adaptation). The three techniques are divided into 2 main techniques, namely; 1 single technique (literal), and 1 couplet technique (reduction + adaptation). The number of single (literal) techniques is 164 data points. The number of couplet techniques (reduction + adaptation) is 18 data points. The translation technique (literal) is the most frequently used translation technique, while the couplet technique (reduction + adaptation) is the least frequently used technique.Keywords: translation techniques, conjunctions, literals, reduction, adaptation, al-Isra’